Application of Surface Electromyography (sEMG) in the Analysis of Upper Limb Muscle Activity in Women Aged 50+ During Torqway Riding - Sylwia Agata Bęczkowska; Iwona Grabarek; Zuzanna Zysk (Sensors)
The aim of this study was to analyze the activation of selected upper limb muscles. For the purposes of this article, we present results concerning the following muscles: triceps brachii, anterior and posterior deltoid, and trapezius in women aged 50 and above during simulated riding of the Torqway device, using surface electromyography (sEMG). The primary objective was to compare muscle activity across two movement phases: active and passive. Accordingly, the following research hypotheses were formulated: muscle activity (measured by RMS values) will be significantly higher during the active phase compared to the passive phase, and MPF (mean power frequency) values will decrease over time, indicating the onset of muscle fatigue. Additionally, the potential of surface electromyography was assessed as a diagnostic tool for evaluating ergonomics and muscle effort in the context of designing personalized mobility devices for older adults. As the study of the Torqway device represents a pioneering research effort, this publication makes a significant contribution to the biomechanical analysis of new forms of active mobility supported by wearable sensor technologies.